Phytoplankton diversity as a bioindicator in river waters - Rinaldi, Rinaldi; Muktitama, Asih Makarti; Nugrahawati, Anis; Yanto, Nopri (Universitas Malikussaleh, 2024)
Water quality can be seen from the diversity of plankton in the waters. Plakton can also be considered as a bioindicator to determine whether the waters are polluted or not. This research was conducted by taking water samples in the waters of the Krueng Pase River and analyzing them in the laboratory. The results of the analysis show that the most common phytoplankton found the type Naviculla sp reached 10%. This type of phytoplankton belongs to the Bacillariophyceae class. Phytoplankton from this group can be a bioindicator of environmental pollution in water.Keywords: Bioindicator; Fitoplankton; Pollutan